(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
This study evaluates the efficiency and spatial homogeneity of the SERS signal in various gold optical antenna morphologies using 4-MBA as a probe molecule. The results demonstrate that AuFON antennas exhibit significantly higher SERS intensity compared to rough surfaces, spherical cavities, and the commercial Klarite system. Additionally, both AuFON and Klarite show improved signal homogeneity. These findings highlight the critical role of ordered nanostructure morphology in enhancing SERS signal amplification and uniformity, positioning AuFON as a promising platform for advanced ultrasensitive molecular detection applications.